Biosafety materials: an emerging new research direction of materials science from the COVID-19 outbreak. (29th May 2020) - Yu, Yingjie; Bu, Fanqiang; Zhou, Huiling; Wang, Yongheng; Cui, Jianxun; Wang, Xing; Nie, Guohui; Xiao, Haihua
Abstract : We first officially propose the brand-new concept of "biosafety materials", which utilizes materials science to solve biosafety problems. Abstract : The coronavirus disease 2019 (COVID-19) pandemic is a serious biosafety event that is causing a severe impact on the global society and economy. Thus, the importance of biosafety is once again being valued worldwide. Due to the outbreak of COVID-19, most national governments have been encouraged to speed up the development of biosafety, which places higher requirements on researchers in biosafety and relevant fields. Many problems have been exposed due to the outbreak of COVID-19, including unavailability of effective drugs and vaccines, difficulty in fast or real-time virus detection, insufficient protective equipment, and shortage of transportation equipment for infected patients. To a certain extent, these biosafety problems are partly due to the limited biosafety-related research in materials science. Currently, the tremendous research efforts in materials science around the world have provided a wide variety of materials with peculiar properties to solve biosafety problems. This review attempts to give a perspective on how the development of novel materials can help scientists tackle the challenges in biosafety. Considering the importance of materials science in the biosafety field, it is urgent for us to officially propose the brand new concept of "biosafety materials", which can be a future scientific discipline that utilizes materials science and theory simultaneously to produce materials, related products, and equipment to solve biosafety problems. Herein, we have aimed to draw worldwide attention on the new discipline of biosafety materials and the active cooperation between materials scientists and biosafety-related scientists to propel its development.